Contextualising black women's identity in South Africa through the apartheid archive's system of racial classification: an intersectional African feminist analysis of race, class, and gender within South Africa's political history. - Grootboom, Lauren (Department of Political Studies, 2025)
Writing against apartheid creates avenues for Black women to reconstruct the South African national history archive with their inclusion while making sense of gender roles in the context of oppressive mechanisms of racism, segregation, and neocolonialism. The critical analysis the formation of how Black women's identity exists at the intersectionality of race, class and gender has been historically refashioned and repurposed through periods of colonialism and the Apartheid system's legal instruments. This research is rooted in African feminist theory of STIWAnism and Nego- Feminism to draw on the structural and intersectional reality of both social and political systems that exist in the past and present African systems that seek to disenfranchise Black women. This research conceptualises Black woman through apartheid system's racial classification by centralising oral history archives as a decolonial methodological tool to understanding how Black women's lived experiences and identities become deeply embedded within the broader social and political systems. The data source for this research consisted of semi-structured open ended oral history interviews which were conducted with participants who are descendants of a Black woman who were racially classified as Coloured instead of Black or Native under the apartheid system of racial classification. Emphasis has been placed on Black women telling their stories and historical experiences by centering memory in revisiting the past as a fundamental contribution thereby building intersectional African feminist archives. Thus, to offer space to make sense of how the intersecting structural issue of oppression is possible in understanding how meaning is made which is extremely instrumental in writing Black women's agency into South Africa's national history. This research therefore aims to write into this literary reality by writing against the apartheid archive by establishing Black women's experiences and the effects of the apartheid system's racial classification in the national history archive. Only once the lived experiences of Black women throughout these oppressive periods of colonialism and Apartheid have been theorised can the process of African feminist emancipation be realised.